DEVELOPING ORAL COMMUNICATION SKILLS IN VOCATIONAL HIGHER EDUCATION: AN EMPIRICAL STUDY OF THE BISPRO TALK LEARNING FRAMEWORK - Refdi Akmal; Muhammad Fadli (University of Kuningan, 2026)
Despite the growing demand for communicative competence in vocational higher education, EFL speaking instruction often remains limited to form-focused and decontextualized practices, resulting in low fluency, confidence, and professional relevance among students. Addressing this gap, the present study investigates Bispro Talk, an English learning framework designed to enhance students’ oral communication skills through vocationally oriented and interactive learning activities. Grounded in communicative competence theory, socio-constructivism, and task-based language teaching, Bispro Talk integrates contextual problem-based discussions, professional role-play, interactive speaking tasks, and structured reflective feedback. Employing a quasi-experimental mixed-methods design, the study involved 70 undergraduate students from the S1 Terapan English for Professional and Business Communication Study Program at Politeknik Negeri Lampung. Participants were assigned to an experimental group (n = 35) receiving Bispro Talk instruction and a control group (n = 35) taught using conventional methods over eight instructional sessions. Quantitative data from pre- and post-speaking performance tests were analyzed using paired and independent samples t-tests, while qualitative data from interviews and classroom observations were examined through thematic analysis. The findings revealed statistically significant post-test improvements in the experimental group across all speaking dimensions’ fluency, pronunciation, vocabulary, grammatical accuracy, and comprehensibility with a large effect size (Cohen’s d = 1.84). Qualitative results further indicated increased speaking confidence, reduced anxiety, and strong learner preference for professionally relevant speaking tasks. The study concludes that Bispro Talk offers an effective pedagogical approach for vocational EFL contexts by promoting authentic, learner-centered oral communication aligned with workplace communication demands.